2012
DOI: 10.1002/art.34669
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of cell‐bound complement activation products enhances diagnostic performance in systemic lupus erythematosus

Abstract: Objective. To determine the value of cell-bound complement activation products in combination with antinuclear antibody (ANA), anti-double-stranded DNA antibody (anti-dsDNA), and anti-mutated citrullinated vimentin antibody (anti-MCV) for the diagnosis of systemic lupus erythematosus (SLE).Methods. This was a multicenter cross-sectional study in which 593 subjects were enrolled (210 SLE patients, 178 patients with other rheumatic diseases, and 205 healthy subjects). Complement receptor 1 levels on erythrocytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
48
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 21 publications
6
48
0
Order By: Relevance
“…The usefulness of these for actual SLE diagnosis may however be questioned. Instead, a panel of parameters including C4d-deposition on B cells and erythrocytes has been suggested 103. Since activation of complement contributes to disease activity, therapeutics such as a monoclonal antibody against C5 (eculizumab) that blocks the pro-inflammatory activation of complement has been tested with promising results in a murine lupus model 104.…”
Section: Complement In Diagnostics and Therapeuticsmentioning
confidence: 99%
“…The usefulness of these for actual SLE diagnosis may however be questioned. Instead, a panel of parameters including C4d-deposition on B cells and erythrocytes has been suggested 103. Since activation of complement contributes to disease activity, therapeutics such as a monoclonal antibody against C5 (eculizumab) that blocks the pro-inflammatory activation of complement has been tested with promising results in a murine lupus model 104.…”
Section: Complement In Diagnostics and Therapeuticsmentioning
confidence: 99%
“…Many patients with SLE experience activation of the classical complement pathway, resulting in reduced complement levels and formation of complement C4 activation products (CBCAPS) that are stably deposited on various cell membranes including erythrocytes (EC4d) and B-lymphocytes (BC4d). [10][11][12] In particular, the deposition of C4d on erythrocytes has a significant impact on erythrocyte membrane deformability, 13 thereby potentially impairing the ability of red blood cells to deliver oxygen to tissues. These CBCAPS were initially reported as valuable in SLE diagnostics, 11 and their performance characteristics were recently validated in a prospective multicentre study.…”
Section: Key Messagesmentioning
confidence: 99%
“…5,6 We have recently reported that significant levels of C4d are present specifically on the surfaces of erythrocytes, 7 reticulocytes, 8 platelets, 9 and lymphocytes 10 of patients with SLE. A recent multicenter study validated cell-bound complement activation products (CB-CAPs) as diagnostic biomarkers for lupus, 11 and additional reports have demonstrated their significant potential as biomarkers of lupus disease activity and stratification. 12,13 In addition to their roles as lupus biomarkers, CBCAPs have been shown to confer functional abnormalities to circulating cells such as erythrocytes and T lymphocytes, suggesting a role in lupus pathogenesis.…”
Section: Introductionmentioning
confidence: 99%